2021
DOI: 10.1007/s11356-021-13483-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in qualitative and quantitative traits of birch (Betula pendula) pollen allergenic proteins in relation to the pollution contamination

Abstract: Birch (Betula pendula) pollen causes inhalant allergy in about 20% of human population in Europe, most of which is sensitive to the main birch allergen, Bet v1. The aim of the study was to find out (i) whether and how the analysed birch individuals differ in regard to composition of individual subunits of pollen proteins and to protein content in these subunits; (ii) whether the level of particulate matter relates to concentration of Bet v1 allergen. Study was performed in Southern Poland, in 2017–2019. Pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The fragility of the exine when pollen is exposed to pollutants (Sénéchal et al, 2015) and the consequent release of intracellular content could influence pollen allergenicity. Some authors reported that high levels of ozone and PM 10 leads to higher levels of Bet v 1 (Beck et al, 2013;Ziemianin et al, 2021) and Phl p 5 ( Ščevková et al, 2020). According to Gilles et al (2018), when plants react to biotic and abiotic stressors, some allergenic proteins and secondary metabolites such as lipid mediators can be produced on pollen.…”
Section: Introductionmentioning
confidence: 99%
“…The fragility of the exine when pollen is exposed to pollutants (Sénéchal et al, 2015) and the consequent release of intracellular content could influence pollen allergenicity. Some authors reported that high levels of ozone and PM 10 leads to higher levels of Bet v 1 (Beck et al, 2013;Ziemianin et al, 2021) and Phl p 5 ( Ščevková et al, 2020). According to Gilles et al (2018), when plants react to biotic and abiotic stressors, some allergenic proteins and secondary metabolites such as lipid mediators can be produced on pollen.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies on the impact of PM10 on Bet v1 concentration in 20 study sites also resulted in the higher level of Bet v1 in the more polluted areas [ 58 ]. Moreover, the pollution level was the more significant factor influencing the Bet v1 concentration in comparison to the year of observations, in spite of that the birch pollen concentrations fluctuated from year to year significantly.…”
Section: Resultsmentioning
confidence: 78%
“…The allergen content of birch pollen was reported to be higher at sites with air pollution. 40 As A. altissima mainly spreads in urban areas, any impact of traffic pollution on its allergenicity should be an issue in further investigations. In our study, individuals from the city and neighboring communities were sensitized to A. altissima at about the same proportion.…”
Section: Discussionmentioning
confidence: 99%